Bamboo-like short carbon fibers@Fe3O4@phenolic resin and honeycomb-like short carbon fibers@Fe3O4@FeO composites as high-performance electromagnetic wave absorbing materials. (August 2020) - Liang, Hongsheng; Xing, Hui; Qin, Ming; Wu, Hongjing
Graphical abstract: Highlights: The samples (SCFs@Fe3 O4 @FeO and SCFs@Fe3 O4 @PR) were successfully prepared. SCFs@Fe3 O4 @FeO and SCFs@Fe3 O4 @PR exhibited excellent EMW absorption performance. The effect of their unique structure on EMW absorption performance was analyzed. Their EABs are 6.1 GHz (SCFs@Fe3 O4 @FeO) and 4.8 GHz (SCFs@Fe3 O4 @PR) at 1.9 mm. Abstract: In recent years, the development of an electromagnetic wave (EMW) absorbing material with low cost, wide bandwidth and strong absorption strength has been widely explored. In this study, SCFs@Fe3 O4 was used as the precursor (S1), and two methods are explored to ameliorate the ultra-high complex permittivity. The method of adding phenolic resin has achieved ideal results, and its bamboo-like SCFs@Fe3 O4 @phenolic resin (PR) (S5) has excellent property. In addition, the electromagnetic properties can be improved by calcining the precursor at 700 °C in a tubular furnace protected by Ar gas, and the obtained honeycomb-like porous SCFs@Fe3 O4 @FeO (S4) composite has superior EMW absorption performance. The excellent EMW absorption performance comes from its unique porous structure. The sample also has a dual loss mechanism of dielectric and magnetic loss. Among them, conduction loss, interfacial polarization, Debye relaxation, hysteresis loss, natural ferromagnetic resonance and exchange resonance play an important role in the process of EMW absorption. It exhibits an effective absorption bandwidth (EAB) of 6.1 GHz with a thin thickness of 1.9 mm. Noting that, by adjusting the thickness (1–5 mm), reflection loss ( RL ) lower than −10 dB can be achieved in the range of 4–18 GHz, which covers the entire C, X and Ku bands. In this study, we not only successfully prepared honeycomb-like porous SCFs@Fe3 O4 @FeO and bamboo-like SCFs@Fe3 O4 @PR, but also proposed two simple methods to solve the excessively high complex permittivity of carbon materials. This has important reference value for the subsequent research of EMW absorbing materials.